Description and phylogenetic position of a new species of Rhyacoglanis (Siluriformes: Pseudopimelodidae) from the Jamanxim River basin - Crispim-Rodrigues, Jefferson Luan [UNESP]; E Silva, Gabriel de Souza da Costa [UNESP]; Shibatta, Oscar Akio; Kuranaka, Mariana [UNESP]; Oliveira, Claudio [UNESP] (FapUNIFESP (SciELO), 2023)
In this study, a new species of Rhyacoglanis is described from the Jamanxim River basin, Tapajós River basin. The new species differs from congeners based on the combination of the following diagnostic characters: two oblique dark bands formed by an agglomerate of melanophores on the predorsal region; dorsal confluence between the dark subdorsal and subadipose bands in large juveniles and adults; ventral confluence between the dark subadipose and caudal peduncle bands; body without conspicuous dark brown spots; complete dark band on caudal peduncle; body with three dark bands; a thin dark caudal-fin band; pectoral-fin spine with anterior serrae distributed along the entire margin; the posterior tip of the post-cleithral process reaching vertical through the base of the dorsal-fin spine; and hypural 5 free of hypural 3 and 4 and pointed caudal-fin lobes. Additionally, our molecular phylogenetic results using ultraconserved elements (UCEs) corroborate the new species as Rhyacoglanis and sister to an undescribed species of Rhyacoglanis from the Xingu River basin. Moreover, as pointed out in previous studies, we confirm Cruciglanis as a sister group to Pseudopimelodus plus Rhyacoglanis.
Keywords: Amazon basin; Bumblebee catfishes; Phylogenomic; Pseudopimelodinae; South America region